Numerical Model for Determining the Magnetic Loss of Magnetic Fluids - Miloš Beković (Materials, 2019)
Magnetic fluid hyperthermia (MFH) is a medical treatment where the temperature in the tissue is increased locally by means of heated magnetic fluid in an alternating magnetic field. In recent years, it has been the subject of a lot of research in the field of Materials, as well as in the field of clinical testing on mice and rats. Magnetic fluid manufacturers aim to achieve three objectives; high heating capacity, biocompatibility and self-regulatory temperature effect. High heating power presents the conversion of magnetic field energy into temperature increase where it is challenging to achieve the desired therapeutic effects in terms of elevated temperature with the smallest possible amount of used material. In order to carry out the therapy, it is primarily necessary to create a fluid and perform calorimetric measurement for determining the Specific Absorption Rate (SAR) or heating power for given parameters of the magnetic field. The article presents a model based on a linear response theory for the calculation of magnetic losses and, consequently, the SAR parameters are based on the physical parameters of the liquid. The calculation model is also validated by calorimetric measurements for various amplitudes, frequencies and shapes of the magnetic field. Such a model can serve to help magnetic fluid developers in the development phase for an approximate assessment of the heating power.